A Test of the Capacity Pressure Hypothesis Within a Simultaneous Equations Model of Export Performance - Dunlevy, James A. (The Review of Economics and Statistics, 1980)
James A. Dunlevy, A Test of the Capacity Pressure Hypothesis Within a Simultaneous Equations Model of Export Performance, The Review of Economics and Statistics, Vol. 62, No. 1 (Feb., 1980), pp. 131-135